Relationship between engine oil viscosity with age and temperature - Nordin, Jamaludin; Othman, Inayatullah; Mohd Jailani, Mohd. Nor; Fauziah, Mat (Universiti Kebangsaan Malaysia (UKM), 2011)
Link to publisher's homepage at http://www.ukm.my/